Leadership for Sustainability: A Case Study of a University Research Center - Christiana Horn; Junghwan Kim (Adult Education Research Conference, 2023)
Research centers provide benefits to an institution, but they struggle with funding. This paper presents how leaders and boards guide a university research center for sustainable organizational development.
Keywords: Leadership; Organizational Sustainability; Research Centers; Higher Education